Maintaining connectivity of mobile nodes using MANET gateway nodes. (2017) - G, Jisha; Samuel, Philip; Paul, Varghese
Mobile users in today's world are in search of wireless communication techniques that provide services anytime, anywhere with less cost and better connectivity. Recent research areas like green cellular networks, device to device communication (D2D) are now focusing on mobile ad hoc networks (MANET), an infrastructure less wireless network that can be deployed with less time and cost, in solving the issues in wireless world. This paper introduces an effective way of integrating MANET with cellular networks using MANET gateway nodes. The proposed architecture helps in maintaining connection between mobile nodes not under the cellular range or experiencing denied services from nearby base stations in densely populated areas. A modified routing protocol which incorporates the gateway discovery and selection is also designed. The new model experience a better packet delivery ratio compared to other models.